Technology for special needs - Cañas, José (Human Technology, 2006)
Human beings use technology to perform all types of tasks. An important issue related to this unquestionable fact is that technologies must be designed so that they can be used by all types of people without any discrimination of age, educational level, abilities, health conditions, and so forth. The term accessibility has been proposed to refer to the parameter that measures the degree to which technology use is not limited by any physical or cognitive barrier. Accessibility is an essential component of the usability parameter that refers to the ease with which a user can learn to operate, prepare inputs for, and interpret outputs of a system or component (International Organization for Standardization.